Marketing Mix Model Development on Private Higher Education in the City of Bandung Indonesia - Pardiyono, Ragil (International Journal of Psychosocial Rehabilitation, 2020)
Growth in the number of Private Higher Education (PTS) in Indonesia has experienced very rapid progress in the past 20 years. According to Kemenristekdikti in Pardiyono and Indrayani [1] for 2017 is 3,276 universities (3,154 PTS and 122 PTN (State Universities)) in Indonesia with 555 university details (17.6%), 78 institutes (2.5%), 1,431 high schools (45.4%), 1,022 academies (32.4%) and Polytechnic 190 (6.0%). Along with the rapid growth of the number of PTS in Bandung resulting in competition among the PTS increasingly competitive. PTS is one of the service industries engaged in education that has different characteristics from other service industries. In fierce competition, research on marketing strategies at tertiary institutions becomes very important to maintain the sustainability of PTS. This study aims to develop a private higher education marketing strategy model by referring to the basic Marketing Mix 7 P strategy model developed by Boom & Bitner (1980) in Groonroos [7], the Relationship Marketing Framework model (Christopher et al. [3]) and the model Student Satisfaction Inventory, developed by Schreiner and Juillerat (1997) in Obiekwe [6] who pay attention to service aspects. Christopher et al [3] divided the marketing mix model into 2 namely external marketing (Product, Place, Price, and Promotion) and Internal Marketing (People, Process, and Customer Service). Whereas Schreiner and Juillerat in 1997 developed a Student Satisfaction Inventory model consisting of 12 variables, namely: 1) Academic Advising and Counseling Effectiveness, 2) Academic Services, 3) Admissions and Financial Aid Effectiveness, 4) Campus Climate Services, 5) Campus Support Services , 6) Concern for the Individual, 7) Instructional Effectiveness, 8) Registration Effectiveness, 9) Responsiveness to Diverse Populations, 10) Safety and Security, 11) Service Excellence, 12) Student Centeredness. The validation testing of the research model was carried out by distributing questionnaires to 396 private tertiary level students and above in Bandung. This research model confirmation uses the Structural Equation Model (SEM) method. This research resulted in Pardiyono's marketing model at private higher education namely that the product has a negative effect on external marketing. Meanwhile, internal marketing is also not significantly affected by Academic Advising and Counseling Effectiveness, Concern for the Individual, and Instructional Effectiveness. The results also explained that in external marketing manifest price variable was the most dominant compared to other variables and in internal marketing the manifest physical variable was the most dominant manifest variable compared to other manifest variables.